2007
DOI: 10.1080/02688690701392899
|View full text |Cite
|
Sign up to set email alerts
|

The role of intrathecal baclofen in the management of primary and secondary dystonia in children

Abstract: Intrathecal baclofen (ITB) is a well-established method of treating spasticity in children with cerebral palsy. In our series, eight children with primary or dystonia secondary to cerebral palsy have benefited from ITB. The observations in this paper are subjective and based on the carer's impressions, but have confirmed the role of ITB in dystonia. Children with dystonia secondary to cerebral palsy benefited most and ITB can be used in these as a single treatment modality. The approach is different in dystoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…The patient was treated with a daily dosage of deferiprone just in between that used in recent pilot trials 15,16 . However, his baclofen dose was higher than that given in previous studies on ITB as a treatment for dystonia 5,19 . No adverse side effects of either drug was reported, aside from decreases in ferritin and transferrin saturation, which were not reflected in hematologic measurements such as MCV, RDW, or hemoglobin level.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The patient was treated with a daily dosage of deferiprone just in between that used in recent pilot trials 15,16 . However, his baclofen dose was higher than that given in previous studies on ITB as a treatment for dystonia 5,19 . No adverse side effects of either drug was reported, aside from decreases in ferritin and transferrin saturation, which were not reflected in hematologic measurements such as MCV, RDW, or hemoglobin level.…”
Section: Discussionmentioning
confidence: 59%
“…Baclofen, a gamma-aminobutyric acid (GABA) receptor agonist, is one of the ‘mainstay drugs’ used to treat dystonia in patients with PKAN 4 . It is often administered via an intrathecal baclofen (ITB) pump, and has been recommended as a safe and effective treatment for dystonia 5 . ITB for the treatment of dystonia was first reported in 1991 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another surgical option to consider for refractory disease is intrathecal baclofen (ITB) therapy. A number of case series have described beneficial outcomes for a variety of secondary dystonias, including those associated with cerebral palsy, traumatic brain injury, PKAN, and Wilson's disease 26, 97–101. In general, ITB appears to be most useful in treating spasticity, with an additional beneficial effect on lower extremity dystonic posturing that may reduce the incidence of a fixed orthopedic deformity.…”
Section: Surgically Intractable Secondary Dystonia: Importance Of Anamentioning
confidence: 99%
“…In addition to its role as a primary treatment modality, the effect of combined DBS and conventional surgical interventions for mixed movement disorder CP subtypes also remains undefined. In one study, Woon et al 52 treated 3 children with dystonia secondary to CP and suggested that DBS may be used to treat the primary functional disease while associated spasticity may be synergistically controlled by intrathecal baclofen infusion. Overall, these studies highlight the significant heterogeneity in movement impairments among children with CP.…”
Section: Spasticitymentioning
confidence: 99%